Alternative reconstruction after pancreaticoduodenectomy - Wayne, Michael G (BioMed Central, 2008)
BACKGROUND: Pancreaticoduodenectomy is the procedure of choice for tumors of the head of the pancreas and periampulla. Despite advances in surgical technique and postoperative care, the procedure continues to carry a high morbidity rate. One of the most common morbidities is delayed gastric emptying with rates of 15%–40%. Following two prolonged cases of delayed gastric emptying, we altered our reconstruction to avoid this complication altogether. Subsequently, our patients underwent a classic pancreaticoduodenectomy with an undivided Roux-en-Y technique for reconstruction. METHODS: We reviewed the charts of our last 13 Whipple procedures evaluating them for complications, specifically delayed gastric emptying. We compared the outcomes of those patients to a control group of 15 patients who underwent the Whipple procedure with standard reconstruction. RESULTS: No instances of delayed gastric emptying occurred in patients who underwent an undivided Roux-en-Y technique for reconstruction. There was 1 wound infection (8%), 1 instance of pneumonia (8%), and 1 instance of bleeding from the gastrojejunal staple line (8%). There was no operative mortality. CONCLUSION: Use of the undivided Roux-en-Y technique for reconstruction following the Whipple procedure may decrease the incidence of delayed gastric emptying. In addition, it has the added benefit of eliminating bile reflux gastritis. Future randomized control trials are recommended to further evaluate the efficacy of the procedure.